2011
DOI: 10.1051/0004-6361/201016008
|View full text |Cite
|
Sign up to set email alerts
|

A search for star-planet interactions in theυAndromedae system at X-ray and optical wavelengths

Abstract: Context. Close-in, giant planets are expected to influence their host stars via tidal or magnetic interaction. But are these effects in X-rays strong enough in suitable targets known so far to be observed with today's instrumentation? Aims. The υ And system, an F8V star with a Hot Jupiter, was observed to undergo cyclic changes in chromospheric activity indicators with its innermost planet's period. We aim to investigate the stellar chromospheric and coronal activity over several months. Methods. We therefore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Wargelin & Drake (2001) advanced this CX X-ray based approach to study the mass-loss rate of late-type dwarfs through the CX interaction of their winds with neutral material of the IS medium (in the same context as heliospheric SWCX emission), but did not detect any significant CX halo in the cases of Proxima Centauri and the M dwarf Ross 154 studied (Wargelin & Drake 2002;Wargelin et al 2008). Recent studies of star-planet interactions in X-rays have mainly focused on the star's X-ray environment to determine the irradiation-driven mass loss of superEarths or the effects of giant planets on the chromospheric and coronal activity (Poppenhaeger et al 2011(Poppenhaeger et al , 2012, concluding that "observational evidence of star-planet interaction in X-rays remains challenging". Hopefully, the next-generation X-ray observatories proposed (e.g., ATHENA) will be able to shed more light in star-planet interactions in extrasolar systems.…”
Section: Discussionmentioning
confidence: 99%
“…Wargelin & Drake (2001) advanced this CX X-ray based approach to study the mass-loss rate of late-type dwarfs through the CX interaction of their winds with neutral material of the IS medium (in the same context as heliospheric SWCX emission), but did not detect any significant CX halo in the cases of Proxima Centauri and the M dwarf Ross 154 studied (Wargelin & Drake 2002;Wargelin et al 2008). Recent studies of star-planet interactions in X-rays have mainly focused on the star's X-ray environment to determine the irradiation-driven mass loss of superEarths or the effects of giant planets on the chromospheric and coronal activity (Poppenhaeger et al 2011(Poppenhaeger et al , 2012, concluding that "observational evidence of star-planet interaction in X-rays remains challenging". Hopefully, the next-generation X-ray observatories proposed (e.g., ATHENA) will be able to shed more light in star-planet interactions in extrasolar systems.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this work is a study of solar analogs, with the sample constructed to mitigate many of the selection biases that affected previous work (e.g., Poppenhaeger & Schmitt 2011). Finally, we use a variety of statistical tests to assess whether hot Jupiter systems display enhanced activity, including the Bayesian linear regression tool of Kelly (2007) that handles both measurement errors and censoring.…”
mentioning
confidence: 99%
“…Single-pointing X-ray observations of planet-bearing stars have been utilized to search for systematic enhancements in L X in hot Jupiter systems, with mixed results (e.g., Kashyap et al 2008;Poppenhaeger et al 2010;Scharf 2010;Poppenhaeger & Schmitt 2011). Such investigations typically statistically average over orbital phase, trading decreased sensitivity to a phase-restricted effect in a given system for a much larger sample size and increased comparative sensitivity to phase-independent or full-surface activity increases; these X-ray surveys probe magnetic or tidal star-planet interaction (presumed one-sided or two-sided, respectively) as well as the potential cumulative tidal influence of hot Jupiters upon their hosts (e.g., stellar spin-up and associated activity rejuvenation; Schröter et al 2011;).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shkolnik et al (2008) found the detections of these signals difficult to reproduce, leading them to speculate that the effect has an "on/off nature" (see Figure 2). Indeed, Poppenhaeger et al (2011) found no variability in the υ And system at the orbital period of its close-in planet in Ca ii H & K or in X-rays, nor did Scandariato et al (2013) in their observing campaign on HD 179949. The difficulty in confirming this mode of interaction since its putative discovery casts doubt on the interpretation that the variations were necessarily due to planetary perturbations.…”
Section: Orbitally Modulated Activitymentioning
confidence: 99%